WAVE OF HASHTAGS ON SOCIAL MEDIA: NETIZENS' ACCEPTANCE OF THE HASHTAG #tidakpercayapolisi - Rachman, Mulia; Santoso, Bagus; Manurung, Afwan Syahril (OPINI: Journal of Communication and Social Science, 2024)
This study analyzes the dynamics of netizens’ reception of the hashtag #tidakpercayapolisi on social media as a reflection of public sentiment toward the Indonesian National Police (Polri). Using a virtual ethnography approach grounded in a critical paradigm, primary data were collected through observation and documentation on social media and analyzed using Klaus Krippendorff’s content analysis to identify communication patterns and key themes. The results reveal a significant gap between Polri’s official narratives and public perceptions, with many netizens adopting an oppositional reception position. Major criticisms include evidence manipulation, corruption, and a lack of transparency in case handling, as well as the use of social media by the public as a platform to mobilize opinion and demand reforms. This study recommends that Polri strengthen communication and transparency through social media, implement internal reforms based on accountability, and utilize technologies such as body cameras and monitoring systems to enhance integrity and public trust in law enforcement institutions.